Beyond instrumental rationality. For a critical theory of freedom - Funk, Jana Katharina (Estudios de Filosofía, 2021)
This article will provide an illustration of Max Weber’s theory of rationalization with a specific impetus on its interdependency with the development of capitalism. Following Horkheimer, I shall critically draw on Weber to outline a theory of human freedom, showing that rationalization not only implies economic and social liberation but entails a totalizing tendency that invades all spheres of socio-political life including people’s mental infrastructure. This mental colonization can be framed as a process of substituting value rationality with instrumental rationality. I will claim that this substitution can be understood as an impediment for human freedom. Following contemporary theories of action (Anscombe, Foot), I will show the centrality of value orientation for understanding human freedom. Therefore, I propose a critical theory of freedom that centers value rational action as realization of freedom and can be understood as emancipative.